Anatomical, physiological, and logistical indications for the open abdomen: a proposal for a new classification system. Issue 1 (December 2016) - Rezende-Neto, Joao; Rice, Timothy; Abreu, Emanuelle; Rotstein, Ori; Rizoli, Sandro
Abstract Background A systematic approach to the appropriate use of the open abdomen strategy has not been described. We propose three fundamental reasons for the use of this strategy, anatomical, physiological and logistical. Anatomical reasons pertain to the inability to bring the fascial edges together including soft tissue defects. Physiological reasons relate to features of systemic dysfunction. Logistical reasons involve any anticipated abdominal re-intervention while preserving fascia. These categories occur either as a single reason or in any combination. Methods A single-center prospective observational study of patients with open abdomens in trauma and acute abdomen. Surgeons were asked to select from the three reasons (single or any combination of) their motivation for using the open abdomen upon completion of the initial operation. Patients were compared using the non-parametric Wilcoxon two-sample test or Kruskal-Wallis test. Chi-square or Fisher's exact test was used for categorical variables; Statistical significance set atP -value ≤ 0.05. Results Forty-five consecutive patients with open abdomens were evaluated (Jan. 1- Dec. 31, 2012). Mean age was 38.8 years, 32 were male, 39 (86.7 %) sustained trauma. The most common single reason for the open abdomen was physiological (24.4 %), 33 patients had multiple reasons, the most common combination being anatomical and physiological (22.2 %). A physiological reason was linked to: lower pH, higher lactate, and lower systolic blood pressure on admission (p  < 0.05). A logistical reason was associated with earlier primary fascial closure, intra-operative packing, and bowel left in discontinuity. Logistic regression and adjusted odds ratio of primary fascial closure was: physiological (0.08, 95 % CI, 0.01–0.92, p  = 0.043); logistical (6.03, 95 % CI, 1.13–32.29, p  = 0.036); and anatomical (0.83, 95 % CI, 0.16–4.18, p  = 0.816). Conclusion We defined three basic indications for the use of the open abdomen, anatomical physiological and logistical. These indications establish a practical and comprehensive terminology that could help to promote appropriate use of the open abdomen.